KINERJA PEGAWAI BIDANG PERLINDUNGAN DAN JAMINAN SOSIALDALAM MENGELOLA DATA TERPADU KESEJAHTERAAN SOSIAL (DTKS) DI DINAS SOSIAL KABUPATEN BENGKULU TENGAH - Yulia Widya Astra; Nursanty (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
The issue of employee performance in carrying out their duties and responsibilities in implementing poverty alleviation programs in the distribution of social assistance to the poor, especially in managing DTKS in Central Bengkulu Regency, is not yet on target. The aim of the research is to describe the performance of employees in the Social Protection and Security Sector in managing DTKS at the Central Bengkulu Regency Social Service. The research method used in this study uses a qualitative descriptive research approach, with informant selection techniques using purposive sampling, data collection techniques using interview, observation and documentation methods and data analysis techniques using data reduction techniques, data display (presentation) and verification techniques. . The research aspect is guided by the theory of Bernardin and Russell in (Huseno 2016) which is collaborated with Regulation Number 30 of 2019 concerning Civil Servant Performance Evaluation. The results of the research show that the performance of employees in the Social Protection and Security Sector in managing DTKS at the Central Bengkulu Regency Social Service is quite good although there are still deficiencies in several aspects of employee performance indicators. The obstacles in this case can be seen firstly, secondly, the quality sub-aspect, the cost sub-aspect, and thirdly, the commitment sub-aspect.